Case Report: Juvenile Myelomonocytic Leukemia Underlying Ornithine Transcarbamylase Deficiency Safely Treated Using Hematopoietic Stem Cell Transplantation - Eguchi, Hiroi; Kakiuchi, Toshihiko; Nishi, Masanori; Kojima-Ishii, Kanako; Nishiyama, Kei; Koga, Yuhki; Matsuo, Muneaki (Frontiers in Pediatrics, 2022)
Background: Juvenile myelomonocytic leukemia (JMML) is a clonal abnormality of pluripotent hematopoietic stem cells that is predominantly found in infants and has features of both myeloproliferative tumors and myelodysplastic syndromes. Estimates have shown that around 20 JMML cases occur annually in Japan. Ornithine transcarbamylase deficiency (OTCD), the most common among the urea cycle disorders, has been found to occur in 1 of 80,000 people in Japan. Case Presentation: A 10-month-old boy with fever, vomiting, and diarrhea for 2 days was referred to our hospital due to the following abnormalities in blood tests: white blood cell count, 48,200/µL; hemoglobin, 9.0 g/dL; and platelet count, 135,000/µL. Bone marrow examination showed that a nucleated cell count of 396,000/mm3 and blasts of 5.0%, as well as decreased mature granulocytes and slight myeroperoxidase stain-negative blasts but no monoclonal cell proliferation with May-Giemsa staining. Colony assay showed proliferation of spontaneous colony and high sensitivity to granulocyte macrophage colony-stimulating factor. Genetic analysis of peripheral blood mononuclear cells showed positive NRAS mutation. The patient was ultimately diagnosed with JMML. Around 170 days after his first hematopoietic stem cell transplantation (HSCT), his JMML relapsed. Shortly after the recurrence, nausea, vomiting, hyperventilation, and decreased vitality were observed, followed by a decrease in the level of consciousness. The patient’s ammonia level was 472 µmol/L. A test for seven different genetic mutations for urea cycle disorder (UCD) showed the presence of c. 119G>A, (amino acid change p. Arg40His). As such, late-onset OTCD was added to his diagnosis. Sodium phenylacetate, L-arginine hydrochloride, and carnitine were continued following the diagnosis of OTCD, after which hyperammonemia had not been observed. Regarding JMML relapse, HSCT was performed on day 405 after the first transplantation. Conclusion: Hyperammonemia should be considered as a differential diagnosis when unexplained and nonspecific symptoms occur during the treatment for hematologic malignancies. Patients should be tested for UCD as a cause hyperammonemia, and treatment for hyperammonemia should be continued until the cause is identified. He is currently in the normal developmental range, has an intact neurological status, and has no second hyperammonemia attack. His JMML has remained in remission for over 3 years.